Comportamento ingestivo e produtividade de vacas das raças Jersey e Holandesa em pastagens de azevém anual - Maixner, Adriano Rudi (2011)
A trial was conducted to evaluate the ingestive behavior, pastures dynamics and productivity of cows of the Jersey and Holstein s breeds grazing annual-ryegrass (Lolium multiflorum) in northwestern Rio Grande do Sul. From April 29th to October 29th of 2010, eleven tester-cows of each breed group, and a variable number of regulator-cows, were managed in rotational grazing with variable stocking rate and received a commercial concentrate at a rate of 1 kg of concentrate for every 3 liters of milk produced up to 15 liters/cow/day. Eight tester-cows of each breed group, two of each stage of lactation, were used in evaluations of ingestive behavior, held on September 27th and October 27th and during the two-day occupation of the paddocks. Pastures management allowed similar conditions between the two tested herds and showed to not limit production of pasture and animals. Adopted supplementation criteria reflected in the provision of large quantities of concentrate for Holstein cows, which had individual milk productions, milk corrected to 4% of fat and total solids higher than the Jersey breed. The Holstein herd was managed with higher stocking rates than the Jersey herd, which reflected directly in superiority on animal production and supply of concentrate per area for the Holstein s herd. For each kilogram of concentrate supplied individually, the Jersey cows had higher individual productions than Holstein, suggesting advantages for the Jersey breed on the conversion of the supplement in animal products and on the economic aspect. The advance of the grazing season and structural changes in the sward conditioned reductions in grazing time and increased rumination, for both breeds, but did not affect the time required for completing other activities. Jersey cows spent more time on grazing activities and less on rumination than Holstein breed, probably to compensate the lower level of supplementation. Only in the second evaluation time (October) difference was found in bite rate between the breeds, with superiority for the Holstein cows, and for both breeds, late lactation cows presented larger number of steps between feeding stations than the cows in early lactation. Additionally, in Holstein, the increase in the number of steps between feeding stations was accompanied by a reduction in sward height of the grazing site visited. Differences between stages of lactation were seen only on variables that represent choices at the level of grazing patches (sward height of the grazing site visited and the number of steps between feeding stations), indicating that adaptations of animals in different physiological stages occur at the level of displacement through the pasture and realization of the bit.